“You should (not) do that”: An Evaluative Model of Normative Appeals (EMNA) - Oceja, Luis (2015)
Normative appeals refer to those messages that indicate that one should (or should not) engage in a certain action in a given situation. According to the psychosocial research, the decision to fulfill a normative appeal depends on both the extent to which it has captured our attention and the evaluation of what we may gain or lose by doing so. However, according to the Evaluative Model of Normative Appeals (EMNA), between these two processes we carry out an evaluation (normative appraisal) that strongly influences the decision that is ultimately made. Specifically, this normative appraisal, which is done in accordance with the dimensions of formality and protection, transforms the appeal into a particular normative representation (i.e., custom, coercive law, prescription, or legitimate law) that, in turn, influences the willingness toward compliance or violation. The results of three studies support these basic premises of EMNA.